A history of the mediaeval church - Frank, Isnard Wilhelm; Bowden, John (London, UK SCM, 1995)
Includes bibliographical references.
Translated from the 2nd ed. of the German : Kirchengeschichte des Mittelalters.-- Dusseldorf : Patmos Verlag, 1990
Keywords: Church history -- middle ages, 600-1500.